Adolescent Pregnancy and Attained Height among Black South African Girls: Matched-Pair Prospective Study. - Elizabeth A Lundeen; Shane A Norris; Reynaldo Martorell; Parminder S Suchdev; Neil K Mehta; Linda M Richter; Aryeh D Stein (PLoS ONE)
Importance The impact of adolescent pregnancy on offspring birth outcomes has been widely studied, but less is known about its impact on the growth of the young mother herself. Objective To determine the association between adolescent pregnancy and attained height. Design Prospective birth cohort study. Setting Cohort members followed from birth to age 20 y in Soweto, South Africa. Participant From among 840 Black females with sufficient data, we identified 54 matched pairs, in which a girl who became pregnant before the age of 17 years was matched with a girl who did not have a pregnancy by age 20 y. Pairs were matched on age at menarche and height-for-age z scores in the year before the case became pregnant (mean 15.0 y). Main outcome measures The two groups were compared with respect to attained height, measured at mean age 18.5 y. Results Mean age at conception was 15.9 years (range: 13.7 to 16.9 y). Mean height at matching was 159.4 cm in the adolescent pregnancy group and 159.3 cm in the comparison group (p = 0.3). Mean attained height was 160.4 cm in the adolescent pregnancy group and 160.3 cm in the comparison group (p = 0.7). Conclusions Among Black females in Soweto, South Africa, adolescent pregnancy was not associated with attained height.